Pengaruh Gaya Penggunaan Anggaran, Kompleksitas Tugas, Kompleksitas Organisasi dan Dukungan Manajemen Terhadap Hubungan Strategi Cost Leadership dan Peningkatan Kinerja di PT Perkebunan Nusantara XI (Persero) - Suwandhi - (Jurnal Aplikasi Bisnis, 2016)
This study aims to examine whether the program of cost leadership affects the labours’ performance of PT Perkebunan Nusantara XI (Persero). Contingency approach is widely used by researchers to determine whether the success of the companies affected by the cost leadership strategy and always have the same effect in each condition. To explain these effects, this study uses four contingency factors, the use of budgets, task complexity, organizational complexity and management support in cost control program in PT Perkebunan Nusantara XT (Persero). The method of data collection is survey methods by using Moderated Regression Analysis (MRA) to test the hypothesis. The results of the study is that budget, task complexity, organizational complexity and management support is not a moderating variable that can strengthen the relationship between cost leadership programs and the improvement of performance in PTPTPNXI (Persero). The results of this study are expected to contribute to the practitioners and to anticipate factors that may affect the company's performance. For academics, these are to explain, how, when, and where the use of the budget, the task complexity, the organization complexity and management support required in order to improve relationship between cost leadership program and the organization success influenced by different conditions.